2012
DOI: 10.1111/j.1461-0248.2012.01744.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable and complex food web structures revealed by exploring missing trophic links between birds and biofilm

Abstract: Food webs are comprised of a network of trophic interactions and are essential to elucidating ecosystem processes and functions. However, the presence of unknown, but critical networks hampers understanding of complex and dynamic food webs in nature. Here, we empirically demonstrate a missing link, both critical and variable, by revealing that direct predator-prey relationships between shorebirds and biofilm are widespread and mediated by multiple ecological and evolutionary determinants. Food source mixing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 47 publications
(60 reference statements)
4
113
0
1
Order By: Relevance
“…Body size is thus a fundamental indicator of trophic level in food webs because it places constraints on many biological variables, including crucial foraging traits (energy content of resources, handling times, attack rates, and prey density) [57][58][59][60]. However, a strong relationship between body size (here, testate amoebae shell length or diameter) and TP cannot be found for consumers that exploit a wide range of prey body sizes [7,59], as shown here with H. papilio and N. tincta. Nevertheless, we found that the size of shell aperture and biovolume were inversely proportional to the TP of testate amoebae in the microbial network, while usually these morphological traits are considered as indicators of high trophic level [12,25,27].…”
Section: Trophic Structure Of the Microbial Food Webmentioning
confidence: 99%
See 2 more Smart Citations
“…Body size is thus a fundamental indicator of trophic level in food webs because it places constraints on many biological variables, including crucial foraging traits (energy content of resources, handling times, attack rates, and prey density) [57][58][59][60]. However, a strong relationship between body size (here, testate amoebae shell length or diameter) and TP cannot be found for consumers that exploit a wide range of prey body sizes [7,59], as shown here with H. papilio and N. tincta. Nevertheless, we found that the size of shell aperture and biovolume were inversely proportional to the TP of testate amoebae in the microbial network, while usually these morphological traits are considered as indicators of high trophic level [12,25,27].…”
Section: Trophic Structure Of the Microbial Food Webmentioning
confidence: 99%
“…Microbial communities are composed of numerous (and often poorly described or altogether unknown) species that can form complex food webs with numerous feeding links. Discovering the structure of these food webs is important because they may affect processes occurring at the population, community, and ecosystem levels [7]. The true trophic position (TP) and diversity in trophic roles of different microbial species and/or species group of different species were, until recently, all but impossible to determine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal stable isotopes are widely used in diet studies in mammals and birds 6,23 , since fractionation is not considered to occur during food assimilation 14 . However, a recent study 7 indicated that while fecal δ 13 C is a reliable proxy for diet in mammals, δ 15 N is altered by digestion for unidentified reasons contingent on diet composition.…”
mentioning
confidence: 99%
“…S29 in Supplementary material) for use in the production of 'fish' feeds (Y. Chen and D. S. Melville, unpublished data), which are part of a growing market for probiotics in aquaculture (Qi et al 2009). The extent of such harvesting and the potential implications for coastal ecology are not known but are potentially significant (Kuwae et al 2012).…”
Section: Intertidal-subtidal Aquaculture and Wild Harvestingmentioning
confidence: 99%